The Influence of Work Culture and Motivation on Employee Performance in the Logistics Affairs of the Police Headquarters Planning and Service Administration Sub-Division - Budiraharjo, Joko; Madiistriyatno, Harries; Soraya, Fatimah; Jati, Prihatina (International Journal of Economics Studies, 2025)
Employee Performance Improvement. 2) To find out and analyze the influence of motivation on improving employee performance. 3) To find out and analyze the Influence of Work Culture and Motivation on Employee Performance in Logistics Affairs, Sub-Section Planning and Administration of Police Headquarters Services. This research approach is quantitative, descriptive and associative. In this study the authors narrowed the population, namely the number of employees of the Logistics Affairs Sub-Division of Planning and Administration of the Police Headquarters Service of 100 employees. The results of this study indicate that: 1) the t-value for the Work Culture variable (X1) is 3.950 while the t-table value for N = 31 is 2.039. So 3.950 > 2.039, then H0 is rejected and Ha is accepted, it can be stated that Work Culture (X1) has a significant effect on Employee Performance (Y). 2) the tcount value for the Motivation variable (X2) is 2,986, while the ttable value for N = 31 is 2,039. So 2,986> 2,039, then H0 is rejected and Ha is accepted, it can be concluded that the motivation variable (X2) partially affects employee performance (Y). 3) ANOVA obtained Fcount value of 14.111 Medium Ftable ( 0.05) for N = 31 of 2.91. So Fcount > from Ftable ( 0.05) or 14.111 > 2.91 with a significant level of 0.000 because 0.000 <0.05, it can be said that Work Culture (X1) and Motivation (X2) together have a positive effect on Employee Performance (Y). Adjusted R Square (R2) value is 0.466. This shows that 46.6% of Work Culture (X1) and Motivation (X2) simultaneously affect Employee Performance (Y) while the remaining 53.4% is influenced by other factors not examined in this study.